Time dependent formation of markers of oxidative stress induced by a high fat diet supplemented or unsupplemented with vitamin E in pigs - Tanja PAJK ŽONTAR; Janez SALOBIR; Vida REZAR (Acta Agriculturae Slovenica, 2009)
The time dependent formation of oxidative damage induced by polyunsaturated fat in the diet was investigated in an experiment with pigs as a model for humans. The role of vitamin E in the prevention of oxidative stress was also studied. Twenty-four growing pigs were penned individually and after an adaptation period divided into three groups. All groups received isocaloric daily rations composed of a basal diet isocalorically supplemented with: starch, linseed oil or linseed oil and vitamin E. Oxidative stress was evaluated by measuring the degree of lymphocyte and granulocyte nuclear DNA damage, concentration of malondialdehyde (MDA) in blood plasma, 24-hour urine MDA excretion rate and concentration of vitamin E isomers in the blood at the beginning, after 24 hours, after 6 days and at the end of the 22 day experimental period. The results confirmed that a high proportion of polyunsaturated fat in the diet increased lymphocyte and granulocyte DNA damage only after 6 days. The lymphocytes appear to be more sensitive to this type of oxidative stress than granulocytes. The MDA concentration in the blood and urinary MDA excretion after 24 hours of oxidative stress seem to be more accurate indicators than the rate of lymphocyte and especially granulocyte DNA damage. Vitamin E supplementation effectively protects the blood cells against increased DNA damage during the whole course of the experiment, but failed to reduce MDA formation significantly 24 hours and 6 days after the beginning of oxidative load. The study further suggests that supplementation of vitamin E is able to completely prevent DNA damage of both types of investigated blood cells at any time, but is only able to reduce the formation of lipid peroxidation products after prolonged treatment.